2016
DOI: 10.3390/ijms17122052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for Rhegmatogenous Retinal Detachment Associated with Choroidal Detachment by Vitreous iTRAQ-Based Proteomic Profiling

Abstract: Rhegmatogenous retinal detachment associated with choroidal detachment (RRDCD) is a complicated and serious type of rhegmatogenous retinal detachment (RRD). In this study, we identified differentially expressed proteins in the vitreous humors of RRDCD and RRD using isobaric tags for relative and absolute quantitation (iTRAQ) combined with nano-liquid chromatography-electrospray ion trap-mass spectrometry-mass spectrometry (nano-LC-ESI-MS/MS) and bioinformatic analysis. Our result shows that 103 differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Yu and colleagues found 516 proteins in vitreous of RRD patients with PVR using SDS-PAGE and reversed-phase liquid chromatography-tandem mass spectrometry [ 22 ]. iTRAQ combined with liquid chromatography-electrospray ion trap-mass spectrometry-mass spectrometry (LC-ESI-MS/MS)was used by Wu and co-workers to identify 103 proteins differentially expressed, including 54 up-regulated and 49 down-regulated proteins, in RRDCD when compared with RD [ 11 ]. More recently, our research group identified 127 proteins in vitreous of RD patients, of which 68 had not yet been found in previous studies, by combining ion exchange chromatography, SDS-PAGE and MALDI-TOF/TOF analysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yu and colleagues found 516 proteins in vitreous of RRD patients with PVR using SDS-PAGE and reversed-phase liquid chromatography-tandem mass spectrometry [ 22 ]. iTRAQ combined with liquid chromatography-electrospray ion trap-mass spectrometry-mass spectrometry (LC-ESI-MS/MS)was used by Wu and co-workers to identify 103 proteins differentially expressed, including 54 up-regulated and 49 down-regulated proteins, in RRDCD when compared with RD [ 11 ]. More recently, our research group identified 127 proteins in vitreous of RD patients, of which 68 had not yet been found in previous studies, by combining ion exchange chromatography, SDS-PAGE and MALDI-TOF/TOF analysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some of them disappeared in severe PVR vitreous or were only detected in vitreous from normal human eyes. Other authors found that TPI1 was downregulated in the vitreous from patients with RRDCD [ 11 ]. Metabolic analysis of vitreous confirms that the glycolytic profile of vitreous is different between RRD and PVR [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, classic two-dimensional gel electrophoresis-based proteomic technologies are still irreplaceable since they provide a visualization map of the proteome and the truncation or modification information of protein isoforms [22][23][24]. Isobaric tags for relative and absolute quantitation (iTRAQ) technology is a high-efficiency nongel quantitative proteomic assay particularly suitable to identify biomarkers in low-abundance proteins [25][26][27][28]. Previous studies on acute aortic dissection reported several potential biomarkers including Lumican, C-reactive protein, and alpha 1 antitrypsin using iTRAQ and differential in-gel electrophoresis technologies [29,30].…”
Section: Introductionmentioning
confidence: 99%